EXPERIMENTAL INVESTIGATION ON THE MECHANICAL BEHAVIOR OF VACUUM INFUSION CFRE COMPOSITE WITH VARYING ORIENTED CARBON FIBER AND ITS APPLICATION ON ACTUAL COMPONENTS - Mujiyono, Mujiyono; Utomo, Yoga Wahyu; Nurhadiyanto, Didik; Wibowo, Heri; Arifin, Achmad (Jurnal Rekayasa Mesin, 2025)
Carbon fiber-reinforced epoxy (CFRE) has better performance properties and is commonly used in the aviation industry. The placement of carbon fiber will affect the mechanical properties of the resulting composite material. The specific application to actual components has yet to be discovered regarding the mechanical capabilities of the CFRE utilization. Therefore, it is essential to investigate further the mechanical behavior of CFRE composites with varying oriented carbon fibers, especially those produced using the vacuum infusion method with a volume fraction of 40%. This study presents an experimental investigation of the CFRE composite with varying oriented carbon fibers in unidirectional, bidirectional, and forged. The result shows composite materials' mechanical characteristics, particularly in the properties of Young's modulus, Poisson ratio, and shear modulus. The unidirectional fiber composites are only suitable for tensile loads in line with the fiber, while bidirectional fiber composites should be cautiously undertaken, as tensile loads applied to the Z-axis may lead to adverse effects; conversely, shear forces can be safely applied to all three axes. The forged fiber direction results in each loading direction having separate capabilities, which are challenging to anticipate. The application of CFRE on an actual component should entail the integration of diverse fiber orientations within a single composite layer, particularly in highlighting manufacturing folding arm components and their adaptability. The test results demonstrate that the maximum load that can be tolerated by the folding arm before failure fulfills the requisite strength criteria, thus allowing for a safety factor of 7.8, which confirms the safety of the CFRE with combined fiber orientation in producing folding arm components.